Endocarditis Infecciosa - Monfragón Bustos, Johel (2019)
Infective endocarditis (IE) is a serious disease, fatal in many cases, its diverse nature makes it a pathology of difficult diagnosis. Although advances in diagnostic techniques and in medical, surgical and critical care interventions have favorably modified the course of this disease, IE still represents a major therapeutic challenge that must be addressed quickly in an integrated way by a specialized team